PENGARUH RETURN ON ASSETS TERHADAP DEBT TO EQUITY RATIO PADA PT. UNILEVER, TBK - NINGSIH, FITRI WIDYA; MUNIARTY, PUJI (Universitas Mahasaraswati K. Mataram, 2024)
The problems with this research are (1) net profit decreases significantly between 2019 and 2022 and (2) total assets decrease between 2020 and 2022. (3) Between 2013 and 2022, the amount of debt fluctuates, increases, or decreases. (4) In 2019–2022, there was another sharp decline in the amount of share capital, which had previously decreased in 2016. This research aims to ascertain and evaluate the strength of the relationship between the debt to equity ratio of PT Unilever, Tbk. This research uses an associative quantitative approach . The data used in the research tool comes from financial report tables describing total assets, total debt, total equity, net profit and total profit in 2013 and ending in 2022. By using purposive sampling, the research sample covers the years 2013–2022, while the population the study covers the years 1982–2022. Document and library research is used in data collection techniques. This research uses various statistical methods to analyze data, including ROA, DER, simple linear regression analysis, correlation, coefficient of determination, and T test analysis. The results show that ROA is not affected by DER at PT. Unilever, Tbk